Cyberbullying and Autistic Traits Across STEM and Non-STEM Professions - Arsić, Bojana B. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Autistic traits occur in the general population and are often linked with a preference for STEM fields. These individuals may also be more vulnerable to cyberbullying. The aim of the study was to determine whether participants engaged in STEM— Science, Technology, Engineering, and Mathematics—occupations and those not engaged in these fields differ regarding cyberbullying and the presence of autistic traits. The study included 206 participants, of whom 92 belonged to the subgroup engaged in STEM occupations (44.7%), and 114 belonged to the subgroup engaged in other occupations (55.3%). Data were collected on participants’ experience of/involvement in cyberbullying, cyber victimization, and the presence of autistic traits. Our study found that individuals engaged in STEM occupations are more often both victims and perpetrators of cyberbullying, and have higher autistic traits than individuals in other occupations. Individuals with autistic traits are more frequently victims of cyberbullying (rs = .18, p = .01). In the subgroup not engaged in STEM occupations, females (U = 948.50, p = .01) and participants aged 25–39 years (H = 9.20, df = 3, p = .03) are more often victims of cyberbullying, whereas males are more often perpetrators of cyberbullying (U = 537.00, p < .001). Males not engaged in STEM occupations have a higher degree of autistic traits compared to females (U = 783.00, p = .009). In conclusion, we highlight the limitations of the conducted research and provide recommendations for future researchers in this field.